(untitled) (JEECS (Journal of Electrical Engineering and Computer Sciences), 2018)
In this study POS (Point Of Sales) Billing System was designed and built with more affordable prices on Restaurant Taxpayers using IoT (Internet Of Thing) devices by utilizing Cloud Computing technology that can sending sales report data in realtime to the server owned by the Probolinggo Regency Financial and Asset Agency. The input from this study is data that is sent in realtime from a billing machine, from a series of tests that have been carried out that can run smoothly, that is proven by measuring data transmission with speed in accessing article data an average of 0.7833 seconds / data transactions compared manually. So that through this application, estimates of regional revenue targets can be monitored directly.